علاقة التحفيز بالرضا الوظيفي لدى العاملين بالمؤسسات الحكومية وبمديرية التربية والتعليم بمحافظة الوسطى في سلطنة عمان - Shekaili Hamad Salim Mohammed
It was obvious through this study which was applied in Al-Wusta Governorate, Sultanate of Oman, as the governorate in which the study was conducted lacks many of the basic elements of life from good housing, recreational places, and service centers. The lack of that governorate led to the emergence of several indicators, including the absence of employees without any reasons, the slowdown in work, and laxity, which led to a lack of productivity. All of this evidence indicates that there are some deficiencies in the incentive systems offered to employees of all categories, whether material or moral, which reflects negatively on job satisfaction with them and the extent of stimulating motivation. So, this study aimed to reveal the relationship of motivation with job satisfaction among workers in government institutions and the Directorate of Education in the Central Governorate of the Sultanate of Oman, To find out the types of material and moral incentives provided to them, in order to build a general incentive system to apply to employees, in a way that contributes to achieve job satisfaction. This study relied on the descriptive and analytical approach. Which based on a codified questionnaire designed by the researcher. Also, this study based on previous relevant studies in order to apply them to the study sample. This questionnaire was validated by applying it to a reconnaissance sample of fifty individuals to calculate the persistence factor "Alpha Cronbach", to apply it to the study sample of two hundred and fifty-five employees, representing all workers in government institutions, including education, where the study sample in this institution accounted for 16 percent of Al-Wusta Governorate, with the rank of director, head department, employee in the study community in the governorate. The results of the study showed a weakness in the performance of material and moral incentives to motivate workers in government institutions in Al-Wusta Governorate of the Sultanate of Oman from the point of view of the study sample of workers in government institutions; As well as in the Directorate of Education in the province.The study results also indicate a weak level of job satisfaction among the study sample. Also, the results of the study also showed a statistically and direct relationship between the areas of motivation and areas of job satisfaction. This study suggested the necessity of paying attention to motivate employees of government institutions due to its positive relationship with raising the level of job satisfaction with them, and also recommended the need to review the mechanisms of motivation of employees of government institutions and restructuring . them to ensure raising the level of job satisfaction for employees